If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + 7) + -1(3x + 4) = 0 Combine like terms: 6 + 7 = 13 (13) + -1(3x + 4) = 0 13 + -1(3x + 4) = 0 Reorder the terms: 13 + -1(4 + 3x) = 0 13 + (4 * -1 + 3x * -1) = 0 13 + (-4 + -3x) = 0 Combine like terms: 13 + -4 = 9 9 + -3x = 0 Solving 9 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -3x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -3x = 0 + -9 -3x = 0 + -9 Combine like terms: 0 + -9 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 3(3z-5)-4(z-8)= | | 120-9=n | | 3+5.4=2 | | 4(2.4)-5=x | | =ln(5y^2+cos(5y)) | | 5x-10=12x-14 | | (M-8)2=13 | | (5x-10)=(12x-14) | | Y=7.50x | | 5x-3x+3= | | 5.5x^2-19.5x+13=0 | | 4(-3u+3)-u= | | ln(3x-5)=1.2 | | 15x+22x=n | | 2+(3+6m)7= | | 38=a-28 | | (9x^2-7x+65)-(11x+8x^2)= | | 8x+4-3x+2=41 | | 8m+3=16 | | f(x)=ln(8x) | | 25a-8b+4c-6a+13b-c= | | 2a+12+a+(3a-9)=117 | | 6-18=m-4+14 | | (-3x^2-2x-2)+(2x^2+4x+4)= | | 9p-4p=-7 | | 27=3/7+6 | | 9x-4=65 | | 6+c=18 | | 3w+15=-4(w-2) | | 3w+15=-(w-2) | | 5-(1-x)=20 | | 7x+5y=-16 |